El carácter sintético de la lengua latina y su legado cultural - Jiménez Juliá, Tomás (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
This paper deals with the possibility of establishing some kind of relationship between those languages which tend towards synthetic syntactic structures (not morphological) and speech communities with social and civil priorities which are equally synthetic and practical, and those languages with a more analytic syntax and communities with more ‘analytic’ civil and cultural priorities. The Roman world and Latin, as well as the British Empire and Modern English, seem to fit in the first frame, whereas Romance languages and European medieval societies, namely Spanish, could illustrate the second.